RESPONSE OF OILSEED RAPE SEED QUALITY PARAMETERS TO CHEMICAL TREATMENT - Ovuka, Jelena (Journal on Processing and Energy in Agriculture, 2024)
Rapeseed is a major oilseed crop that has various uses in the food, feed, and industrial sectors. The first condition for successful production and achieving high yields is to provide high-quality seeds, which, in addition to high seed vitality, also implies good seedling protection. The goal is to ensure an optimal number of plants per hectare, which is also a basic prerequisite for achieving high yields. Quality seed treatment has proven to be the best solution for plant protection in the initial stages of development. The seeds were treated with fungicides with the a.i. carboxin + thiram and fluopicolide + fluoxastrobin, as well as an insecticide with a.i. flupyradifuron, and the control was untreated seed. Treatments had a great influence on germination energy, seed germination, number of abnormal seedlings, length and weight of seedlings. The fungicidal fluopicolide + fluoxastrobin treatment had the greatest positive effect on most of the tested parameters, while the carboxin + thiram + flupyradifuron treatment had the greatest negative effect on the seed germination parameter.